SYNTHESIS OF SINGLE-STAGE CIRCUITS OPERATIONS IN NON-BINARY ADDITORS - Gumenyuk , V. A. (Problems of Informatization and Management, 2005)
It is proposed to use a single-stage output matrix and, in certain cases, a switching unit. A method of composing matrices is described, which takes into account the features of the adopted alphabet.